Do Basic Psychological Needs and Self-Determined Motivation Outweigh Physical Activity Volume and Body Composition in Explaining Subjective Well-Being Among Community Gym Users? - Marco Batista; João Freitas; Vera Simões; Ana Conceição; Marta Martins; Eduardo Teixeira; Paulo Rosa; Hugo Louro (International Journal of Environmental Research and Public Health, 2026)
This study examined the relative contribution of sociodemographic, psychological, behavioral, and physiological factors to subjective well-being (SWB) among community gym users and investigated the indirect association between basic psychological need satisfaction and SWB through self-determined motivation. A cross-sectional study was conducted with 348 adults (31.53 ± 12.86 years) recruited from community gyms in Portugal. Participants completed validated measures of basic psychological need satisfaction, motivational regulation, life satisfaction, and positive and negative affect. Moderate-to-vigorous physical activity (MVPA) was assessed through self-reported weekly physical activity, and body composition through bioelectrical impedance. Hierarchical multiple linear regression and mediation analysis were performed. Missing data were addressed using multiple imputation. Psychological variables produced the largest increase in explained SWB variance (ΔR2 = 0.173, p < 0.001). MVPA added only 0.2% (ΔR2 = 0.002, p = 0.478), while body composition indicators added 1.0% (ΔR2 = 0.010, p = 0.303). The final model explained 21.7% of SWB variance. A significant indirect association through self-determined motivation was observed (B = 0.228, 95% CI [0.139, 0.324]). Psychological variables provided greater explanatory information about SWB than MVPA or body composition. The findings highlight the relevance of psychological experiences in exercise settings, while the cross-sectional design precludes causal interpretations.